Intelligent mobile learning tool for grammar learning (i-MoL tool). - Shuib, Munir (Universiti Sains Malaysia, 2017)
Helping students retain what they have learnt is one crucial aspect to be focused on in education. According to the Ebbinghaus forgetting curve, without effective learning reinforcement, students will forget 80% of what they have leamt within 31 days. The traditional face-to-face classroom setting alone is not enough to help students retain their existing knowledge, including in learning English grammar. Despite the needs for effective learning reinforcement, learning English grammar effectively should be fun and challenging. It has to be in line with the leaming needs of students in today's technological environment who would prefer more digital motivation,flexibility and mobility.